Research on the security of national secret algorithm based compute first networking - Jie PAN; Lan YE; Pengfei ZHANG; Zhonggui BU (Dianxin kexue)
With the promotion of national secret algorithm, in-depth research on the arithmetic network was carried out, a more efficient and reasonable security scheme for the arithmetic network was proposed, ensuring the data security and privacy of the arithmetic network with the help of the state secret algorithm.The main elements of the design program included: Supporting arithmetic demand and cryptographic invocation through the underlying resources, the arithmetic orchestration layer provided the ability to orchestrate data arithmetic, meanwhile, the arithmetic scheduling layer intelligently discerned the optimal nodes for arithmetic resource scheduling and allocation; the cryptographic reinforcement layer used the national secret algorithm based on hardware support with the help of public key cryptosystem, hash function, digital envelope, homomorphic encryption, blockchain and other technologies.Focusing on arithmetic network access security, transmission security, data security and privacy protection aspects of security implementation.An architecture and application form was innovatively proposed to guarantee the data security of the arithmetic network, which could meet the needs of the application layer arithmetic in the scenarios of big data, intelligent technology, etc..The security of the arithmetic network is enhanced by empowering the arithmetic network through the state-secret algorithm.